College-Aged Males Experience Attenuated Sweet and Salty Taste with Modest Weight Gain. Issue 10 (23rd August 2017) - Noel, Corinna A; Cassano, Patricia A; Dando, Robin
Abstract: Background: Human and animal studies report a blunted sense of taste in people who are overweight or obese, with heightened sensitivity also reported after weight loss. However, it is unknown if taste changes concurrently with weight gain. Objective: This study investigated the association of weight gain with changes in suprathreshold taste intensity perception in a free-living population of young adults. Methods: Taste response, anthropometric measures, and diet changes were assessed with a longitudinal study design in first-year college students 3 times throughout the academic year. At baseline, 93 participants (30 males, 63 females) were an average of 18 y old, with a body mass index (in kg/m 2 ) of 21.9. Sweet, umami, salty, sour, and bitter taste intensities were evaluated at 3 concentrations by using the general Labeled Magnitude Scale. Ordinary least-squares regression models assessed the association of weight gain and within-person taste change, adjusting for sex, race, and diet changes. Results: Participants gained an average of 3.9% in weight, ranging from −5.7% to +13.8%. With each 1% increase in body weight, males perceived sweet and salty as less intense, with taste responses decreasing by 11.0% (95% CI: −18.9%, −2.3%; P = 0.015) and 7.5% (95% CI: −13.1%, −1.5%; P = 0.015) from baseline, respectively. Meanwhile, females did not experience this decrement, and even perceived a 6.5% increase (95% CI: 2.6%, 10.5%; P = 0.007) in sour taste with similar amounts of weight gain. Changes in the consumption of meat and other umami-rich foods also negatively correlated with umami taste response (−39.1%; 95% CI: −56.3%, −15.0%; P = 0.004). Conclusions: A modest weight gain is associated with concurrent taste changes in the first year of college, especially in males who experience a decrement in sweet and salty taste. This suggests that young-adult males may be susceptible to taste loss when gaining weight.